LED Intercanopy Lighting in Blackberry During Spring Improves Yield as a Result of Increased Number of Fruiting Laterals and Has a Positive Carryover Effect on Autumn Yield - Rivas, Anabel; Liu, Kang; Heuvelink, Ep (Frontiers in Plant Science, 2021)
High market price and low availability of local winter and spring production has stimulated production of blackberries in glasshouses at northern latitudes. For this production, light is the main limiting factor. We investigated the potential of intercanopy lighting (ICL) using light emitting diodes (LEDs) to improve blackberry fruit yield in a crop with a spring and an autumn production cycle. During the spring production cycle three light treatments were applied: only natural light (no ICL), 93 µmol m-2 s-1 ICL or 185 µmol m-2 s-1 ICL In summer the lateral shoots were cut back and 93 µmol m-2 s-1 ICL was applied to all plants after cutting back, investigating a possible carryover effect of supplemental light in spring on autumn production. Fresh fruit yield in spring increased by 79% and 122% with 93 and 185 µmol m-2 s-1 ICL, respectively, compared to no ICL. This represents 3.6 % and 2.8% increase in harvestable product for every additional 1% of light. Maximum photosynthetic capacity for leaves at 185 µmol m-2 s-1 ICL was about 50% higher, and LAI was 41% higher compared to no ICL. ICL increased the number of fruiting laterals per cane, and this explained 75% of the increase in yield. ICL at 185 µmol m-2 s-1 resulted in a higher yield compared to no ICL, primarily as a result of higher total dry matter production. Furthermore, a higher fraction of dry matter partitioned to the fruits (0.59 compared to 0.52) contributed to yield increase, whereas fruit dry matter content and fruit quality (sugar and acid content) was not affected by ICL. Averaged over the 3 light treatments autumn yield was 47% lower than spring yield. Autumn yield was 10% higher for plants at ICL 93 µmol m-2 s-1 in spring and 36% higher for plants at 185 µmol m-2 s-1 in spring compared to no ICL in spring. This increased autumn yield was caused by more fruiting laterals (less necrotic buds). It is concluded that management practices in spring can have a carryover effect on the autumn production.